Diversity of Trees and Birds in Kuching City, Sarawak, Malaysia - Stephanie, Judi (Universiti Malaysia Sarawak (UNIMAS), 2020)
Urbanization changes the landscape of an area and in the process indirectly change the natural habitat of wildlife, affecting their diversity and population. The urban landscape of a city can be categorized into Green zones, Residential zones, Industrial zones, and Commercial zones. The objectives of this study were to determine the species diversity of trees and birds in these zones of Kuching City; Importance Value of trees by each zones and bird species adaptation in term of structure uses, feeding guild, and urban group; the correlation between tree species origin and the bird adaptation level. In this study, six replicates in Green zone and Residential zone, seven replicates in Commercial zone and five replicates in Industrial zone were established and used for both trees and bird survey. Observation were made using transects surveys (24 transects). The data collection for bird was conducted monthly for six months in 2016 followed by the tree survey until September 2017. Species diversity were measured in Shannon Index and Simpson Diversity Index for both tree and birds, while the significant difference of species diversity between zones was measured by using Chi-square test. Sorensen Index was also used to identify the level of species similarities for trees and birds. Results indicate that diversity index was higher in Green zone for both tree (H: 4.125; D: 0.030) and bird (H: 2846; D: 0.1072). Sorensen Index showed highest similarity of tree (0.436) between Residential and Industrial zones whereas for birds, higher similarities (0.8254) were observed in Industrial and Commercial zones. The Fabaceae family has the highest Relative Dominance in all zones (Green: 29.8%; Commercial: 28.62%; Industrial: 66.79%) except in Residential zones where Bignoniaceae is the highest (38.43%). Feeding guild showed birds sighted belong to the granivorous group has higher Relative Dominance in three zones (Residential: 55%; Commercial: 40%; Industrial: 58%) except in Green zones where 36% of birds belong to the omnivorous guild. Higher number of tree (exotic or native) can increase the population of urban avoider but reduce the population of urban exploiters. The pattern of bird population in Kuching city showed more urban exploiter and less urban avoider in all zones should be taken seriously. Urban avoider had higher potential to face extinction as these birds are very sensitive to development and depend more on natural resources compared to human-modified resources.